Role of Women’s Organisations in Women’s Education in India, 1917–1947 - Mathew, Priyanka (JOURNAL OF INDIAN EDUCATION, 2020)
It is the women’s movement, which in itself is a social movement. The objective of the study is to provide a comprehensive analysis of the activities of the Women’s Organisations as well its educational activities. The idea is to note the educational contribution of the Women’s Organisations. The research questions include how far the Indian Women’s Organisations empowered women and how did the Indian Women’s Organisations support women’s education and the methodology is based on historical method which is based on researching documents, contemporary newspapers in the archives, and the libraries. The core findings reveal that women’s organisations are no longer elitist. But, initially, they did focus on the upper caste or upper class women. In time, these organisations became non-communal. Over a period of time, these women’s organisations became more multi-class. A group of professionals namely, doctors, teachers, academics and social workers actually laid the foundation of the women’s education. Even post independence, women’s education was about empowering the family not so much about the individual woman. The study captures the period between 1917 to 1947, which was about actually the period, when the Women’s Indian Association was set up in 1917. There was also the 1947 period which is associated with the freedom of the nation. This period is a breaking point in History where women witnessed changes in their political rights through the right to vote and also set the ball moving towards the Hindu Code Bill which changed the social and economic rights of women. In the Indian context, women’s movement has been classified into three phases. The first phase was related to the movement by social reformers.